Foraging enrichment alleviates oral repetitive behaviors in captive red‐tailed black cockatoos (Calyptorhynchus banksii). Issue 1 (4th November 2019) - Fangmeier, Melissa L.; Burns, Alicia L.; Melfi, Vicky A.; Meade, Jessica
Abstract: The relationship between inadequate foraging opportunities and the expression of oral repetitive behaviors has been well documented in many production animal species. However, this relationship has been less‐well examined in zoo‐housed animals, particularly avian species. The expression of oral repetitive behavior may embody a frustrated foraging response, and may therefore be alleviated with the provision of foraging enrichment. In this study, we examined the effect of different foraging‐based enrichment items on a group of captive red‐tailed black cockatoos who were previously observed performing oral repetitive behavior. A group of six cockatoos were presented with five foraging enrichment conditions (no enrichment (control), sliced cucumber, fresh grass, baffle cages, and millet discs). Baseline activity budgets were established over a 10‐day preintervention period and interventions were then presented systematically over a 25‐day experimental period. This study demonstrated that the provision of foraging interventions effectively increased the median percentage of time spent foraging compared to control conditions (range, 5.0–31.7% across interventions vs. 5.0% for control), with two of the interventions; grass and millet discs, significantly decreasing the expression of oral repetitive behaviors (control = 16.6 vs. 8.3% for both grass and millet discs). Finally, a rapid‐scoring method utilized by zookeepers during the study proved to be a useful proxy for the amount of time the cockatoos spent interacting with the foraging interventions and overall time spent foraging. Abstract : Four foraging interventions were successfully provided to cockatoos to alleviate oral repetitive behavior (a); (b) sliced cucumber, (c) grass grown in pots and provided in clumps (also shown are fresh turf squares provided post‐study in a similar manner), (d) baffle cages, and (e) millet discs. Research Highlights: The provision of foraging enrichment effectively increased the time spent foraging of captive red‐tailed black cockatoos and significantly decreased the expression of oral repetitive behaviors. A rapid‐scoring method used by zookeepers during the study proved to be a useful proxy for the amount of time the cockatoos spent interacting with the foraging interventions and overall time spent foraging.